Experimental Study on Light Concrete Properties Using Bottom Ash of Thermal Power Stations - Demchenko, Oksana; Shulgin, Volodymyr; Petrash, Ruslan (International Journal of Engineering and Technology, 2018)
This paper presents the most optimal compositions of light concrete utilizing bottom ash for manufacturing the energy efficient wall products. Bottom ash usage as a filler instead of quartz sand acts as utilization of wastes which has a positive impact on ecology. It’s been experimentally investigated the influence of the amount of cement and water on strength, density, water consumption, and thermal conductivity of light concrete manufactured using the bottom ash from thermal electrical stations as a filler. Using the STATISTICA 12 software there were obtained the precise values of coefficients that allow achieving the maximum strength. It’s been manufactured the energy efficient wall blocks based on bottom ash with the concrete compression strength class ofLC 20/22.  The conclusions quantify the results of these studies.